Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Study on the O2 migration pathway and critical product formation mechanism in the water immersion coal oxidation - Guo-yu Shi; Xin-xiao Lu; Guan Wang; Zhao Yang; Long He; Rui-nan Zhang (Fuel, 2026)

Advanced electric field technologies for postharvest preservation of fresh fruit and vegetables: Applications, mechanisms and future perspectives - Ben Yu; Dongyang Xu; Tingshi He; Jiangshan Qiao; Junhu Cheng; Xin-An Zeng; Rui Wang (Postharvest Biology and Technology, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Enhanced photothermal catalytic oxidation of cyclohexane over a S-scheme CoAl2O4/WO3-x heterojunction with LSPR effect-induced hot electrons - Kuan Wang; Kai-Xiong Dai; Yu-Rui Chao; Yue Yang; Xin-Peng Li; Zhen-Hong He; Weitao Wang; Huan Wang; Zhao-Tie Liu (Journal of Environmental Chemical Engineering, 2026)

Enhanced stability of CH3NH3PbBr3 quantum dots for electrochemiluminescence detection of saxitoxin - Yu Han; Ting Zhang; Rui Kang; Xin Gao; Jiawei Liu; Qingchun Yin; Hongmei Cao; Long Wu (Food Chemistry, 2026)

Ecological risks of olivine with different particle sizes and dosages on planktonic ecosystems during ocean alkalinization - Zi-Rui Ding; Xin-Ming Wu; Ping Li; Xin-Yu Qian; Chang Liu; Ming-Hao Yin; Chun-Feng Qu; Zhihan Cao; Jinho Jung; Ling Liu; Zhi-Hua Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Temperature-responsive topology regulation for fire-safe, high-strength polyamide 66 via a low-barrier phosphonate spacer - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Ya-Dong Wang; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Oxygen-vacancy-mediated BrO3− electroreduction: Positively charged microenvironment enables directional diffusion and spontaneous adsorption - Xiangbin Huang; Yue Cheng; Zhipeng Luo; Ruiqi Zheng; Yangying Zhao; Salman Farissi; Rui Liu; Gong Zhang; Xin Yu; Huabin Zeng (Chemical Engineering Journal, 2026)

Soliton solutions, spectral classification and asymptotic analysis for the shifted nonlocal modified nonlinear Schrödinger equation with nonzero background - Xin-Yu Liu; Yan-Nan Zhao; Rui Guo (Wave Motion, 2026)

Paleoenvironmental response in the South China Sea from the Middle Miocene Climatic Optimum to Middle Miocene Climate Transition: Geochemical records from an isolated carbonate platform - Ning Guo; Wei Jiang; Tianlai Fan; Shendong Xu; Rui Wang; Jian-xin Zhao; Yue-xing Feng; Kefu Yu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Early Cretaceous Jehol Biota in the Qinling Orogenic Belt: palaeobiogeographical and palaeoecological implications - Siyu Song; Xin Zhang; Xiao Teng; Ting Li; Tingting Yu; Jiahao Li; Yan Xue; Peihan Liu; Rui Fang; Xiangdong Zhao; Daran Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Lactobacillus helveticus MB2-1 powders prepared using different drying strategies reshape dominant intermolecular interaction patterns and structural network formation during fermentation of coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Yibo Shi; Xiaotong Hao; Shiyuan Feng; Chunling Meng; Jiamin Xu; Di Yu; Tao Lin; Kai Ma; Changliang Zhang; Mingsheng Dong; et al. (Food and Bioproducts Processing, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

Engineered probiotic carriers enregulate coordinated cuproptosis and ferroptosis with immune activation against bladder cancer - Anguo Zhao; Rongkang Li; Rui Liang; Qi Zhuang; Yang Liu; Dashi Deng; Peng Yu; Lei Peng; Hongbo Xu; Jun Zhang; Zhangxin He; Xin Chen; et al. (Chemical Engineering Journal, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Improving spatiotemporal assessment of watershed soil redistribution by integrating source-sink theory into a multi-model framework - Rui Tan; Yu Tao; Geng Guo; Kaiwen Huang; Zicheng Liu; Lin Chen; Xin Liu; Jie Lin (Journal of Hydrology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Genetic discrimination of the Dongshan Pb-Zn-Cu deposit based on sphalerite chemistry - Yi-Chen Chen; Shi-Jiong Han; Cheng-Gang Cao; Jun-Wei Bo; Yu-Rui Yuan; Ming-Yu Tang; Jin-Xin Yuan (Journal of Geochemical Exploration, 2026)

Pulsed electric field processing of buffalo milk with retained Joule heating: Microbial efficacy, bioactive protein retention, and flavor profiling - Lang-Hong Wang; Jia-Hong Li; Xu-Rui Li; Yu-Xi Hu; Rui Wang; Xin-An Zeng (Innovative Food Science & Emerging Technologies, 2026)

Lactiplantibacillus plantarum SP055 pretreatment attenuates experimental colitis in association with partial preservation of epithelial integrity and microbial-metabolic homeostasis - Jianwei Zang; Xiaotong Hao; Yibo Shi; Xia Fan; Yimeng Kou; Xiaogan Zhao; Qiaoya Mo; Di Yu; Jiamin Xu; Chunling Meng; Chang Xu; Luyao Xiao; et al. (Food Bioscience, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Mechanistic study on direct oxidation of xylose to xylonic and xylaric acids in base-free medium - Yinghao Wang; Wei Yu; Zhaozhe Li; Rui Min; Wenmao Zhang; Chunmei Li; Feng Du; Wenjuan Yan; Xin Jin; Chaohe Yang (Chemical Engineering Journal, 2026)

Plastisphere-driven pollutant enrichment and harmful bacteria proliferation: Emerging ecological risks to Danjiangkou reservoir's water security - Tao He; Zhi-Min Xu; Le-Yi Cheng; Yi-Cai Zhang; Shuang Wang; Xiao-Yan Zhang; Xi Yang; Yu-Ting Hou; Si-Yi Wang; Xin-Yue Hu; Xin-Rui Zhou; Yong-Hong Ma; et al. (Marine Pollution Bulletin, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

A Variogram Model Based on Spatial Decay of Gravity Anomaly Covariance - Xiao-yu Xie; Kai-xin Luo; Ju-liang Cao; Shao-kun Cai; Rui-hang Yu; Qi-qin Hu; Yan Guo; Bai-nan Yang (Applied Geophysics, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

A versatile colorimetric array sensor based on FeCu-based prussian blue analogue heterostructures for efficient discrimination of tetracycline antibiotics and rapid identification of urinary tract infection pathogens - Dan Wu; Xin-Yu Cheng; Chao-Man Wang; Ya-Nan Kong; Shu-Chang Zhao; Rui-Lin Liu (Journal of Hazardous Materials, 2026)

Endogenous nitric oxide production induced by pulsed electric field modulates postharvest quality of mango - Ben Yu; Runyu Yao; Dongyang Xu; Tingshi He; Wenhao Xiao; Wenhong Gao; Junhu Cheng; Zhong Han; Xin-An Zeng; Rui Wang (Food Research International, 2026)

Effects of Hofmeister cation series induced by different alkalizers on the production, structural and functional characteristics of low-sodium soy protein fractions - Yu Peng; Rui Wang; Mo Li; Xin Wen; Yuanying Ni; Sirinan Lasrichan (Food Hydrocolloids, 2026)

Long working hours increase the risk of insufficient dietary diversity: Findings among online ride-hailing drivers - Binshuo Hu; Cheng Chang; Xin Song; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Hong Yu; Li Guan; Dongsheng Niu; Jue Li; Rui Guan; Tenglong Yan (Appetite, 2026)

Copper nanoparticles enhance azo dye decolorization by Shewanella putrefaciens CN32: enhanced effect and underlying mechanisms - Bai-Hang Zhao; Rui-Xuan Liu; Bing-Lin Zhang; Xin-Yu Zhang; Xu-Ming Liu (Journal of Environmental Sciences, 2026)

Salinity decrease leads to recovery of filamentous bacterial bulking in moderately halophilic aerobic granules: Unraveling the role of fungi - Ze-You Lu; You-Wei Cui; Ya-Nan Mi; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Jia-Ying Li (Bioresource Technology, 2026)

Hydrogenophaga pseudoflava widely distributed in wastewater treatment plants exhibiting heterotrophic nitrification-aerobic denitrification: From characterization to genomics - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Jia-Ying Li; Ya-Nan Mi; Xin-Yu Gu (Bioresource Technology, 2026)

Developmental light colour influences adult phototaxis and locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Zi-Yu Guo; Xu-Hui Guo; Sheng-Yu Hou; Ke-Jing Feng; Yu-Xin He; Han-Ning Wu; Xin-Hui Chen (Behavioural Processes, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Dynamic error elimination method of strapdown gravimeter based on artificial neural network - Shao-kun Cai; Yang Yu; Rui-hang Yu; Zhi-ming Xiong; Ju-liang Cao; Yan Guo; Bai-nan Yang; Kai-xin Luo; Mei-ping Wu (Applied Geophysics, 2026)

Physicochemical properties, antioxidant activity, antibacterial properties, and fruit preservation potential of black soldier fly chitosan films - Bin-Qiao Yuan; Ting-Hao Yu; Jun-Kui Huang; Xin-Rui Ren; Run-Jia Wang; Guo-Xin Huang; Nortoji A. Khujamshukurov; Da-Wei Huang; Jin-Hua Xiao (Food Bioscience, 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Deletion of the SHORT Syndrome Gene Prkce Results in Brain Atrophy and Cognitive and Motor Behavior Deficits in Mice - Yu-Long Bao; Wei-Peng Duan; Yan Yang; Zhijie Lin; Ying Shen; Rui Zheng; Xin-Tai Wang (Neuroscience Bulletin, 2026)

Red–Blue LED Ratios Regulate Vegetative Growth, Photosynthetic Performance, and Anthocyanin Accumulation in Red Lettuce (Lactuca sativa cv. ‘Lolla Rossa’) under Controlled Conditions - Hadiqa Anum; Xiaokai Liang; Rui-feng Cheng; Yu-xin Tong (Journal of Plant Growth Regulation, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Near-surface ground ice map of the Northern Hemisphere - Bingquan Wang; Youhua Ran; Xin Li; Jan Hjort; Olli Karjalainen; Qingbai Wu; Yu Sheng; Huijun Jin; Defu Zou; Lin Zhao; Rui Ma; Ziyong Sun; et al. (Science Bulletin, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Long-term reclamation enhances soil organic carbon accumulation via mitigating salinity and alkalinity in coastal saline soils - Wei Zhu; Shiguo Gu; Xin Zhang; Xuan Yu; Shuanghuang Yu; Xiangping Wang; Rui Jiang; Xiangtian Meng; Rongjiang Yao (Agriculture, Ecosystems & Environment, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

Alleviating effects and mechanism of Lacticaseibacillus paracasei BHP06 on the allergic reactions induced by ovalbumin - Xiang-Ge Xin; Yue Meng; Jun Meng; Jun Xi; Chang-He Ding; Rui-Han Ge; Yu-Tong Bai; Ming-He Li (Food Bioscience, 2026)

Pulsed electric field facilitated fibrillation of soy protein isolate: preparation, characterization, and functional properties - Dong-Yang Xu; Ben Yu; Wen-Hao Xiao; Zhong Han; Rui Wang; Xin-An Zeng (Food Hydrocolloids, 2026)

Alterations in cardiovascular biomarkers and gut microbiome associated with night shift work: Insights from the Chinese platform workers study - Tenglong Yan; Li Rong; Siyuan Wang; Xin Song; Binshuo Hu; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Rui Guan; Hong Yu; Dongsheng Niu; Ying Zhang (Environmental Research, 2026)

Comprehensive observations of carbonyls in the Northern slope of the Tianshan Mountains: Characteristics, reactivity and sources - Kexin Wang; Minghao Dong; Hanran Liu; Xin Zhang; Yunfeng Li; Yafei Wang; Rui Gao; Jingjing Zhang; Yurong Li; Yu Chen; Zhaojiang Li (Air Quality, Atmosphere & Health, 2026)

Automatic first-arrival picking based on clustering selection - Lei Gao; Xin-rui Luo; Yu Fang; Mei Yan (Applied Geophysics, 2026)

Perspectives on the role of postbiotics in meat and meat products: Current status and future trends - Du-xin Jin; Gui-peng Zou; Rui Liu; Man-gang Wu; Qing-feng Ge; Hai Yu (Meat Science, 2026)

Exogenous melatonin alleviates heat stress-induced metabolic slowdown affecting broiler growth by improving lipid metabolism - Fei Song; Binglin Wang; Xin Kang; Aige Han; Huiyuan Rui; Xiangyang Xu; Yi Guo; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2026)

Alkalinity change induces succession of heterotrophic and autotrophic nitrifying bacterial communities: Comprehensive insights on the mechanism - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Xin-Yu Gu; Jia-Ying Li; Ming-Xin Su (Journal of Environmental Management, 2026)

Investigation of water and oxygen influence on the coal thermal decomposition entire process kinetic mechanism and gas product source tracing - Xin-xiao Lu; Guo-yu Shi; Rui-nan Zhang; Shuo Wang; Long He; Guan Wang (Fuel, 2026)

NCOA4-mediated ferritinophagy regulates AgNP-induced ferroptosis in lung cells - Rui Zhang; Haitao Yang; Menghao Guo; Shuyan Niu; Yu Ma; Xin Shen; Liqing Wu; Chenyu Liu; Mengjing Cui; Tianshu Wu; Yuying Xue (Food and Chemical Toxicology, 2026)

Long-term removal of root carbon inputs has a great negative impact on grassland soil bacterial diversity, network stability and carbon and nitrogen cycling function - Rongrong Wu; Jilin Zhang; Haiyan Zhang; Xiao Zhang; Biao Dong; Yu Shi; Xin Jing; Rui Xiao; Cancan Zhao (Applied Soil Ecology, 2026)

Identification of disease-associated gene expression signatures for mechanistic insights and drug prediction in dilated cardiomyopathy-induced heart failure - Wei Yu; Shuai Xu; Xin Tan; Hangyao Zhang; Ruohan Ma; Yiyao Zeng; Anchen Xu; Honghui Tang; Qin Rui; Yahui Song; Yafeng Zhou (Molecular and Cellular Biochemistry, 2026)

Gyrotropic magnetic effect in black phosphorus irradiated with bicircular light - Fangyang Zhan; Xin Jin; Da-Shuai Ma; Jing Fan; Peng Yu; Dong-Hui Xu; Rui Wang (Science Bulletin, 2026)

Microalgae-bacteria interactions in acidic mining pit lakes: Community assembly and environmental drivers - Meichen Wang; Jin Wang; Xin Pan; Zijie Yu; Ziyi Li; Rui Deng; Zhengbo Yue (Process Safety and Environmental Protection, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

Pulsed electric fields as a green alternative to chemical treatment: Toward enhanced molecular interactions and performance in biodegradable preservation films - Rui Wang; Pei-Feng Guo; Ying Xu; Xing-Chan Xie; Dan-Dan Lin; Yu-Wei Wu; Dong-Yang Xu; Lang-Hong Wang; Xin-An Zeng (Chemical Engineering Journal, 2026)

Expression of Beta vulgaris betaine aldehyde dehydrogenase 1 (BvBADH1) confers salt tolerance in tobacco (Nicotiana benthamiana) - Ming Wei; Xiang-Yu Chen; Meng-Li Li; Hao Li; Xin-Rui Wu; Guo-Qiang Wu (Physiology and Molecular Biology of Plants, 2026)

Soluble TREM1 Contributes to Aging-Related Neurodegeneration via ROBO2/ERK Pathway - Jing-Wen Qi; Xin-Yu He; Yu-Cheng Gu; Zi-Jian Luo; Rui Duan; Ying-Dong Zhang; Yi Xie; Teng Jiang (Molecular Neurobiology, 2026)

Novel interface-enhanced bimetallic nanozyme-mediated magnetic integrated nanoplatform for integrated prevention and control of pathogenic bacteria - Xiaoyu Yu; Xin Zhang; Yuwei Ren; Rui Jiao; Hui Li; Mengyu Li; Weichao Wu; Na Ling; Danfeng Zhang; Jianghua Cheng; Yingwang Ye (Analytica Chimica Acta, 2026)

Screening and characterization of marine cyanobacteria for dairy farm wastewater treatment: Nodosilinea sp. E11 as a promising candidate for phycoremediation - Meiqi Zhang; Rui Xin; Yu Wang; Keqiang Zhang (Journal of Cleaner Production, 2025)

Heterogeneous electro-Fenton like process by iron-doped nickel phosphide catalyst for dibutyl phthalate degradation within a wide pH range - Ruo He; Rui Zhou; Hang Xu; Li-Kun Xu; Chen-Yi Xu; Lian-Feng Mei; Wen-Zhao Zhou; Hong-Yu Meng; Xin Zhang (Journal of Environmental Chemical Engineering, 2025)

DoLPHiN: a proposed architecture and technical implementation of a database of structural and functional properties of natural polysaccharides with health benefits - Yefu Xin; Yongling Cao; Shuheng Yang; Junhao Hu; Miao Tian; Jian Dai; Jing Shi; Bingcong Yu; Nike Gu; Xiangxu Hu; Rui Zhu; Qianni Duan; et al. (Food Chemistry, 2025)

Recent advances and perspectives in coordination polymer-based fluorescent sensors for vitamin detection - Zi-Hao Zhao; Zhi-Wei Liu; Xin-Rui Xu; Qian-Yu Yang; Zhao-Yang Tong (Chemical Engineering Journal, 2025)

The comprehensive review of eucalyptol: synthesis, metabolism, and therapeutic applications in disease treatment - Bin Yao; Bin He; Jiahua Peng; Xin Song; Rui Zhao; Yu Sun; Yanfang Zhang (Molecular Biology Reports, 2025)

Wheat straw incorporation and nitrogen fertilization increase antibiotic resistance gene abundance and dissemination potential in agricultural soil - Feng-Hua Wang; Rui-Ao Ma; Zi-Teng Liu; Xin-Di Zhao; Ruibo Sun; Wenxu Dong; Yuming Zhang; Min Qiao; Si-Yu Zhang (Soil Ecology Letters, 2025)

Differential response patterns of bacterial communities in seawater and sediments to the Chaetomorpha valida bloom in sea cucumber Apostichopus japonicus aquaculture ponds - Hongxia Zhang; Kexin Xu; Ronglian Xing; Linqian Wang; Renyu Liu; Xin Wang; Lihong Chen; Rui Li; Zhen Yu; Xuebin Cao; Cao Cheng; Qun Su (Marine Pollution Bulletin, 2025)

Transcriptomic analysis of the mechanism of male reproductive injuries caused by the mixture of three phthalates in rats - Ling-Zi Xia; Jun-Zhe Yue; Li-Jun Wu; Qian-Ying Jin; Yi-Pei Yang; Jing-Yang Yu; Rui-Zhe Pan; Xin Zhang; Xiao-Ying Wu; Jiayin Zhu; Hai-Tao Gao (Toxicology and Applied Pharmacology, 2025)

Evaluation of efficacy of intensity measures for fast and reliable seismic fragility analysis of bridge columns - Jian-Cheng Dai; Dong-Sheng Wang; Xiao-Yu Chen; Wei-Jian Tang; Rui Zhang; Ying-Xin Hui (Soil Dynamics and Earthquake Engineering, 2025)

The potential of anthraquinone-2-sulfonate (AQS) for “shell breaking” of iron-coated denitrification granular sludge - Xin-Rui Zhang; Zhi-Han Xi; Zi-Jun Yan; Xin-Tao Liu; Ying Wang; Run-Mei Li; Zi-Yue Li; Ke-Yu Wu; Ren-Cun Jin; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Management, 2025)

Assessment of the effects of oligosaccharide supplementation on the structure of lactic-fermented soy protein gel and its allergenic epitopes - Xinran Guo; Xiaocui Lu; Di Yu; Xia Fan; Wei Li; Xin Rui (Food Hydrocolloids, 2025)

Anthocyanins in action: physiological, biochemical, and molecular strategies for mitigating climatic stress in eco-friendly crop production - Hadiqa Anum; Shumila Ishfaq; Rui-feng Cheng; Yu-xin Tong (Physiology and Molecular Biology of Plants, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Surface oxygen vacancies and their synergy effect with Pt in Pt/CoCeOx promoting H2 activation for furfural hydrogenation - Yu Fang; Rui Wang; Min Tian; Shanyu Yi; Luna Ruan; Xin Duan; Huan Zhang; Zhiqing Yang; Hengqiang Ye; Lihua Zhu (Chemical Engineering Journal, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Inhibition by dissolved organic matter of the degradation of purine compounds by the sulfate radical - Shuangshuang Cheng; Rui Cui; Jinpeng Yu; Yujie Zhao; Xin Yang (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Modulating the metal–support interaction of Pt/CeO2 catalysts for enhanced chemodynamic therapy for lung cancer thearanostics - Meijuan Ding; Tao Jia; Rui Xin; Guanghua Cui; Xiaoke Sun; Jialu Guo; Lili Feng; Yu Yang (Chemical Engineering Journal, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Application and identification of monoclonal antibody targeting a novel epitope on p72 protein of African swine fever virus - Yu Dai; Xin Deng; Qi Wang; Ke Yang; Shuqing Yang; Xinran Li; Xinlei Liu; Yuanyuan Yang; Yu Gu; Yi Zheng; Rui Wu (Veterinary Microbiology, 2025)

Mitigation of arsenic uptake and accumulation in rice grains by applying husk-derived silicon in a synergistic way: Evidence from pot and field trials - Xianghong LI; Xin WANG; Xionghui JI; Jingmin YANG; Yunping YU; Rui HUANG; Bo PENG; Baoshan XING (Pedosphere, 2025)

Effects of reversing the light-dark cycle on growth performance and intestinal health in heat-stressed broilers - Huiyuan Rui; Xiangyang Xu; Fei Song; Aige Han; Meiwei Lv; Xin Kang; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Metabolic network evolution of hazardous waste by material flow analysis integrated with complex network analysis - Liping Zhan; Rui Zhao; Xin Xiong; Yang Yu; Qihao Zeng (Journal of Environmental Management, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Assessment of Thermal Vulnerability and Analysis of Influencing Factors in Urban Functional Areas of Foshan City, China - Xinyue Wang; Jun Yang; Rui Zhang; Jiaxing Xin; Wenbo Yu; Jiayi Ren; Xiangming Xiao (Chinese Geographical Science, 2025)

Target analysis of per- and polyfluoroalkyl substances in surface water: Occurrence, seasonal trends, and risk-based prioritization in the Minjiang River - Hui Zhang; Xin-Yue Wang; Yu-Hua Zheng; Jing-Run Hu; Xiao-Lin Li; Hong-Ling Yin; Rui Xiao; Xiao-Lan Zhu; Ting Chen; Huan Chen (Science of The Total Environment, 2025)

Biochar-loaded iron oxide as a novel electrode for the electro-Fenton degradation of sulfaquinoxaline: Performance evaluation, mechanistic insights, and toxicity transformation - Xiaowen Li; Sufang Wang; Jierong Zheng; Xin Fan; Jilong Qin; Yu Yang; Aijuan Zhou; Rui Li; Houfen Li; Xingfa Li; Xiuping Yue (Journal of Environmental Management, 2025)

Ultra-stable CO2-aqueous foams for carbon sequestration and internal mineralization in cellular cements - Dingqiang Fan; Xue-Sen Lv; Jian-Xin Lu; Rui Yu; Wei She; Juhyuk Moon; Takafumi Noguchi; Chi Sun Poon (Chemical Engineering Journal, 2025)

Responses of an invasive plant Alternanthera philoxeroides to cadmium, nutrient availability and water temperature - Zi-Yang Xie; Zhi-Hang Liu; Xin-Yue Gu; Yuan-Yuan Qin; Yu-Ting Du; Jin Yan; Rui Zhang; Chao Si (Aquatic Botany, 2025)

Macoligophones A–I, prenylated acetophenone dimers and monomers from Maclurodendron oligophlebium - Jing-Jing Qi; Yu-Nan Qian; Ying Li; Xiang-Yu Liu; Rui-Yao Fu; Zheng-Hui Huang; Jian-Min Yue; Jin-Xin Zhao (Phytochemistry, 2025)

Intelligently responsive PVDF MF membrane with improved antifouling and easy-cleaning performance for efficient separation of oil-water emulsion - Aida Aibulatova; Lin Yu; Zhen-Liang Xu; Jia-Rui Yang; Rui Jia; Yin-Xin Fang (Journal of Environmental Chemical Engineering, 2025)

SfM on-the-fly: A robust near real-time SfM for spatiotemporally disordered high-resolution imagery from multiple agents - Zongqian Zhan; Yifei Yu; Rui Xia; Wentian Gan; Hong Xie; Giulio Perda; Luca Morelli; Fabio Remondino; Xin Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Bimetallic organic framework-derived multifunctional signal marker-driven ultra-magnetic nanoplatform for sensitive detection and efficient sterilization of methicillin-resistant Staphylococcus aureus - Xin Zhang; Xiaoyu Yu; Yuwei Ren; Rui Jiao; Hui Li; Xiyan Zhang; Ganghui Li; Xiyang Xia; Na Ling; Danfeng Zhang; Yingwang Ye (Chemical Engineering Journal, 2025)

Versatile Dual-Emissive Boron-Nitrogen Co-Doped carbon Dots: Unlocking efficient electroluminescent Light-Emitting diodes with breakthrough EQE Approaching 7% - Ming-Zhu Li; Hong-Ji Tan; Qi-Rui Liang; Jie-Rong Yu; Peng Huang; Xiao-Qi Lai; Chun-Fa Wen; Chun-Sing Lee; Qing-Xiao Tong; Jing-Xin Jian (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Ensemble framework for multistep carbon emission prediction: an improved Bi-LSTM model based on the Bayesian optimization algorithm and two-stage decomposition - Qi Song; Yu-Long Bai; Rui Wang; Xiao-Xin Yue; Wen-Hui Liu (Stochastic Environmental Research and Risk Assessment, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Recent advances and future prospects of wearable sensors based on nanomaterial sensing mechanisms for biosafety monitoring - Xiaoyu Yu; Hui Li; Junwen Wang; Xin Zhang; Rui Jiao; Yuwei Ren; Danfeng Zhang; Na Ling; Yingwang Ye (Chemical Engineering Journal, 2025)

Diatomic "catalytic/co-catalytic" Fe/Mo catalysts promote Fenton-like reaction to treat organic wastewater through special interfacial reaction enhancement mechanism - Zhen Liu; Xin-Yi Xu; Fei Xu; Rui-Dian Su; Bin Li; Fang Zhang; Xing Xu; Yan Wang; De-Fang Ma; Bao-Yu Gao; Qian Li (Water Research, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Selective preparation of aromatic compounds from catalytic pyrolysis polyester coating over Ni, Mo and Co metal modified ZSM-5 - Zhen-Qiang Yu; Yao-Xin Xiao; Dong Liang; Che Zhao; Zhen Huang; Gang-Qi Cheng; Rui Shan; Hao-Ran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Magnetic graphene-enhanced exonuclease III assisted amplification strategy driven carbon nanozyme for tri-mode detection of Escherichia coli O157:H7 - Yuwei Ren; Lulu Cao; Zongyang Li; Xin Zhang; Hui Li; Rui Jiao; Xiaoyu Yu; Zhao Liang; Ganghui Li; Xiyang Xia; Na Ling; Danfeng Zhang; et al. (Food Chemistry, 2025)

Co-culture fermentation of Debaryomyces hansenii and Bacillus atrophaeus alleviates quality deterioration of litchi fruit by ameliorating microbial community diversity and composition - Zhen Li; Yu Wang; Rui Li; Yuxin Hu; Xin Wang; Wen Li; Yuanzhi Shao (Food Microbiology, 2025)

Catalyst pre-diffusion: An efficient strategy for the construction of COF nanofiltration membranes - Lin Yu; Aida Aibulatova; Zhen-Liang Xu; Li Li; Changqing Hao; Rui Jia; Yin-Xin Fang; Yan Zheng; Yong-Jian Tang (Desalination, 2025)

Dynamic characterization of the changes in intestinal fungi and fecal metabolites during the reproductive cycle of sows - Jin-Wen Su; Xin-Wen Hou; Shuo Liu; Yu Chen; Ji-Xin Zhao; Xiao-Xuan Zhang; Hong-Bo Ni; He Ma; Rui Liu (Veterinary Research Communications, 2025)

Microrna363-5p targets thrombospondin3 to regulate pathological cardiac remodeling - Yu-kun Ma; Xin-yi Han; Shu-huai Zan; Hui-ting Liu; Xue-yan Zhou; Dan-xue Zhao; Rui Xing; Peng Zhao (Molecular and Cellular Biochemistry, 2025)

Characterization of the gut microbiota in drug abuse: prediction, prevention, and personalized medicine to benefit affected populations - Xin Wang; Ya-Jie Yu; Cai Liao; Xiao-Ru Liu; Rui Yu; Yun Wang (EPMA Journal, 2025)

Numerical and experimental studies on the hydrodynamic performance of a composite cylindrical perforated-wall caisson breakwater - Zi-bo Xia; Xin-yu Wang; Xiao Liu; Rui-jia Jin; Bao-lei Geng; Yong Liu (Ocean Engineering, 2025)

Experimental investigation on ammonia‑nitrogen adsorption performance of ZSM-5 molecular sieve prepared from coal gangue and fly ash - Qing-Wei Li; Ye-Rui Zhu; Li-Feng Ren; Wen-Ting Xu; Yu-Xin Miao; Yang Xiao; Cai-Ping Wang (Journal of Water Process Engineering, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Aeration strategies for microalgae in wastewater treatment: Enhancing pollutant removal and community dynamics - Pan Li; Yajun Luo; Fei Ming; Jingxian Zheng; Zhicheng Pan; Rui Wang; Yanqing He; Miao Zhou; Xin Xiong; Chi Zhang; Yu Lei; Zhaoqi Wang; et al. (Journal of Environmental Management, 2025)

Functional characterization and site-directed mutagenesis of a novel UDP-glycosyltransferase from Panax japonicus var. major - Lu Mou; Yang Zhang; Yu-Xin Zhuang; Rui-Fang Ren; Ran Xu; Ling Yang; Shao-Peng Zhang; Deng-Xiang Du (Planta, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

The reverse-reduction effect of dissolved organic matter on the degradation of micropollutants induced by halogen radicals (Cl2•- and Br2•-) - Shuangshuang Cheng; Rui Cui; Yangjian Zhou; Yu Lei; Ni Wang; Yanheng Pan; Xin Yang (Water Research, 2025)

Platinum-based fluorescent nanozyme-driven “loong frolic pearls” multifunctional nanoplatform for tri-mode ultrasensitive detection and synergistic sterilization of Burkholderia gladioli - Rui Jiao; Yuwei Ren; Xiyan Zhang; Hui Li; Ying Zhan; Xin Zhang; Xiaoyu Yu; Na Ling; Yingwang Ye (Food Chemistry, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

ZnCur nanoparticle-enhanced multifunctional hydrogel platform: Synergistic antibacterial and immunoregulatory effects for infected diabetic wound healing - Yan-Wen Ding; Zhi-Wei Zhang; Xin-Yu Cui; Rui-Yang Hu; Yang Li; Si-Da Huang; Si-Qi Du; Jin-Wei Dao; Dai-Xu Wei (Chemical Engineering Journal, 2025)

Efficient resource recovery from food waste digestate via hydrothermal treatment and its application as organic fertilizer - Hong Chen; Jun Sheng; Qinhui Ye; Jun Li; Xin Yu; Hanyue Wu; Rui Zhang; Shiyi Zhao; Xiaoming Zou; Xiang Li; Gang Xue; Baoling Yuan (Bioresource Technology, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

SOTHE: SOlar-terrestrial habitability explorer - Jiajia Liu; Bingkun Yu; Fuchuan Pang; Siteng Fan; Lixiang Gu; Lingping He; Yajuan Lei; Bo Li; Rui Li; Yiren Li; Dongdong Liu; Kai Liu; et al. (Advances in Space Research, 2025)

A systemic review of yak milk and its products on the Qinghai-Tibet Plateau: Unique products, chemical composition, biological activities, and microbial composition - Zhiqiang Liang; Xiaoqian Chen; Xinyu Wang; Xiaoxi Qi; Lina Zhang; Yu Xin; Zhenyu Yang; Rui Fan; Yang Li; Libo Liu; Chun Li (Trends in Food Science & Technology, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

Assessing the climatic niche changes and global invasion risk of Solanum elaeagnifolium in relation to human activities - Xin-Di Li; Yu Chen; Chun-Ling Zhang; Jia Wang; Xing-Jiang Song; Xian-Rui Zhang; Zhi-Hong Zhu; Gang Liu (Science of The Total Environment, 2024)

Effective purification of Fe/V as spherical phosphosiderite and porous vanadium oxyhydroxide from waste vanadium-bearing slag - Zhu Suiyi; Su Ting; Lan Xin; Htet Oo Kaung; Zheng Minglin; Wang Tianzhu; Luo Wenjing; Zhou Rui; Yang Weilu; Chen Yu (Journal of Water Process Engineering, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Insight into the effect of potassium amyl xanthate on copper pollution caused by chalcopyrite bio-dissolution - Rui Liao; Jun Wang; Shichao Yu; Xin Sun; Shitong Liu; Baojun Yang; Guanzhou Qiu (Journal of Environmental Management, 2024)

High-performance COFs composite nanofiltration membrane fabricated by organobase catalyst - Lin Yu; Jia-Yue Dai; Zhen-Liang Xu; Yin-Xin Fang; Rui Jia; Yong-Jian Tang (Desalination, 2024)

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Oreonectes yuedongensis (Cypriniformes, Nemacheilidae), a new freshwater fish species from the Lianhua Mountains in eastern Guangdong, China - Chang‐Ting Lan; Tao Luo; Xin‐Rui Zhao; Jing Yu; Ning Xiao; Jiang Zhou (Journal of Fish Biology, 2024)
In this work, we describe a new species of the genus Oreonectes , Oreonectes yuedongensis sp. nov., collected from the Lianhua Mountains in eastern Guangdong, China. Phylogenetic trees constructed based on the mitochondrial cytochrome b ( Cyt b ) gene showed that this new species represents an independent evolutionary lineage, with uncorrected genetic distances (Kimura 2‐parameter model) from congeners ranging from 5.1% to 8.3%. In addition, nuclear DNA analysis indicated O. yuedongensis as an independent lineage separate from its closely related species. Morphologically, the new species can be distinguished from other six species in the genus Oreonectes by a combination of serial characters. The description of this new species suggests that it is necessary to reassess the biodiversity of Oreonectes platycephalus as a complex, especially in the middle reaches of the Pearl River near the border between Guangdong and Guangxi. Morphological and genetic evidence supports O. yenlingi as a synonym of O. platycephalus .

Sappanone A ameliorates acute lung injury through inhibiting the activation of the NF-κB signaling pathway - Jing Du; Piao Zhou; Xin Zhao; Yu-Ting He; Cheng-Shi He; Rui-Yu Wang (Toxicology and Applied Pharmacology, 2024)

Regulation of anthocyanin synthesis in red lettuce in plant factory conditions: A review - Hadiqa Anum; Kun Li; Javaria Tabusam; Said Abdelhalim Abdelaty Saleh; Rui-feng Cheng; Yu-xin Tong (Food Chemistry, 2024)

Screening high-efficiency promoter to construct trans-vp28 gene Anabaena sp. PCC7120 against white spot syndrome virus of Litopenaeus vannamei - Xin-Yu Chen; Dian-Jiang Yu; Rui Jia (Fish & Shellfish Immunology, 2024)

The CYP3A inducer dexamethasone affects the pharmacokinetics of sunitinib by accelerating its metabolism in rats - Guang-rong Lu; Rui-zhen Wang; Xin-yu Zhao; Jun-er Xu; Cheng-ke Huang; Wei Sun; Rui-jie Chen; Zhe Wang (Chemico-Biological Interactions, 2024)

Simulation of a cold spell in Guangdong-Hong Kong-Macao Greater Bay Area with WRF: Sensitivity to PBL schemes - Rui Xin; Xian-Xiang Li; Yu Du; Minghua Li; Lup Wai Chew (Atmospheric Research, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

The presences of water in the generation of calc-alkaline I-type granitic magmas at continental arc: Insight from Neoproterozoic Ailaoshan magmatism at the southwestern margin of the Yangtze Block, South China - Bin Huang; Rui Li; Nimat Ullah Khattak; Xin-Yu Cai; Yang Zhang; Wei Wang (Precambrian Research, 2024)

Exploring Jiangshui-originated probiotic lactic acid bacteria as starter cultures: Functional properties and fermentation performances in pear juice - Du-xin Jin; Yu-xuan Jin; Wei Zhang; Wei Cao; Rui Liu; Man-gang Wu; Qing-feng Ge; Hai Yu (Food Bioscience, 2024)

Metabolomics combined with intestinal microbiota analysis to reveal the effects of Inonotus hispidus on chronic kidney disease caused by high-protein diet - Xin Pang; Zitao Guo; Long Ao; Yong Huang; Bo Hu; Zhenghua Gu; Yu Xin; Zhongpeng Guo; Rui Zhu; Moying Li; Liang Zhang (Food Bioscience, 2024)

An efficient Au/ZnO catalyst for the photocatalytic conversion of methane to formaldehyde - Yan-Qun Chen; Lei-Xin Mao; Rui-Xin Zhang; Xin-Yu Zhang; Zhi-Hua Gao; Lei Liu; Wei Huang; Zhi-Jun Zuo (Chemical Engineering Journal, 2024)

Effects of Spraying Allantoin at Different Stages on Inorganic Nitrogen Assimilation, Endogenous Hormones, Yield, and Quality of Sugar Beet in Saline-Alkali Land - Xin-Rui Yu; Jia-Nan Zhao; Yan-Long Zhuang; Ling-Hua Zhao; Chao Wang; Xiao-Fei Yang; Yu-Bo Wang; Cai-Feng Li (Sugar Tech, 2024)

Optimizing waste leachate treatment for environmental and economic sustainability: Insights from a bottom-up study of over 300 cities - Qian-long Han; Hai-long Zhao; Guo-xia Wei; Han-qiao Liu; Yu-wen Zhu; Tong Li; Yan-fei Lin; Xin-rui Su (Sustainable Production and Consumption, 2024)

Selective metallization of polymer based on nanoscale tungsten oxide laser activators for advanced electronics - Haoran Xu; Feifan Yu; Jin Feng; Rui Xu; Jiameng Huang; Jia-Xin Wang; Tao Zhou (Chemical Engineering Journal, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

OsSPL11 positively regulates grain size by activating the expression of GW5L in rice - Xinhai Zeng; Kai Fan; Yu Shi; Rui Chen; Wanyu Liu; Xin Wang; Guixiang Ye; Wenxiong Lin; Zhaowei Li (Plant Cell Reports, 2024)

Farrerol Alleviates Cerebral Ischemia–Reperfusion Injury by Promoting Neuronal Survival and Reducing Neuroinflammation - Rui Zhao; Xin Zhou; Zhiyuan Zhao; Wenhao Liu; Mengfei Lv; Zhaolong Zhang; Changxin Wang; Tianli Li; Zixiong Yang; Qi Wan; Rui Xu; Yu Cui (Molecular Neurobiology, 2024)

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Effects of air frying on protein digestive properties in scallop (Patinopecten yessoensis) adductor muscles and the mechanisms involved - Zi-Ye Wang; Ying Luo; Rui Zheng; Shuo Lv; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Probing rotaxane dynamics with 19F NMR/MRI: Unveiling the roles of mechanical bond and steric hindrance - Yu Li; Man Luo; Mou Jiang; Rui Zhou; Wanrong Yang; Shenhui Li; Fang Wang; Lijun Zhu; Pei He; Minghui Yang; Xin Zhou; Zhong-Xing Jiang; et al. (Analytica Chimica Acta, 2024)

Targeting gut microbiota for immunotherapy of diseases - Ya-Jie Yu; Xiao-Dong Liu; Cai Liao; Rui Yu; Xin Wang; Ming Li; Yun Wang (Archives of Toxicology, 2024)

Quercetin regulates dendritic cell activation by targeting STAT4 in the treatment of experimental autoimmune encephalomyelitis - Fang Zhou; Yu-Xin Guo; Rui Gao; Xiao-Yu Ji; Yu-Xuan Tang; Li-Bin Wang; Yuan Zhang; Xing Li (Toxicology and Applied Pharmacology, 2024)

Victoria amazonica-inspired sandwich-structure interfacial solar steam generator - Junjie Pan; Xin Zhang; Chenglong Zhang; Wenfeng Hu; Siyi Bi; Huiqi Shao; Nanliang Chen; Rui Yu; Jinhua Jiang; Guangwei Shao (Chemical Engineering Journal, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Multi-omics Analysis of Volatile Flavor Components in Pacific Chub and Spanish Mackerel during Freezing using GC–MS–O - Yi-Zhen Huang; Yu Liu; Rui Zhu; Xiaoxiao Ma; Songlin Xin; Beiwei Zhu; Xiu-Ping Dong (Food Chemistry, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

An observational prospective study based on a large cohort of HIV-negative neurosyphilis patients with particular reference to the Jarisch-Herxheimer reaction - Rui-Rui Peng; Juan Wu; Wei Zhao; Lin Zhu; Zhifang Guan; Xin Gu; Mei Shi; Junjun Yu; Yanchun Cheng; Pingyu Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The purpose of this study is to outline a complete picture of Jarisch-Herxheimer reaction (JHR) in the central nervous system among HIV-negative neurosyphilis patients. Methods A prospective study cohort of 772 cases with almost all stages of neurosyphilis depicted the features of JHR including occurrence rate, risk profiles, clinical manifestations, medical management and prognosis. Results The total occurrence rate of JHR was 9.3% (95% CI, 7.3-11.4%), including 4.1% (95% CI, 2.7-5.6%) with severe JHR. The reaction started 5 h after treatment initiation, peaked after 8 h, and subsided after 18 h. Patients with severe JHR experienced a longer recovery time (26 h). Patients with general paresis (OR = 6.825), ocular syphilis (OR = 3.974), pleocytosis (OR = 2.426), or a high CSF-VDRL titre (per log 2 titre increase, OR = 2.235) were more likely to experience JHR. Patients with general paresis had an 11.759-fold increased risk of severe JHR. Worsening symptoms included cognitive impairment, mania, nonsense speech, and dysphoria, while symptoms of hallucination, urination disorder, seizures, myoclonus, or aphasia appeared as new-onset symptoms. Neurosyphilis treatment did not need to be interrupted in most patients with JHR and could be reinstated in patients with seizures under supportive medication when JHR subsided. Conclusion Severe JHR displayed a 4.1% occurrence rate and clinicians should pay particular attention to patients at a higher risk of JHR. The neurosyphilis treatment regime can be restarted under intensive observation for patients with severe JHR and, if necessary, supportive medication should be initiated and continued until the end of therapy.

Protective effect of resveratrol on nickel-refining fumes-induced inflammatory damage - Yu-Lin Pan; Rui-Ze Wu; Yao Fu; Rui Xin; Yong-Hui Wu (Cell Biochemistry and Biophysics, 2024)

Cadmium interacts with nitrogen level and nitrogen form to affect the growth of an invasive plant Alternanthera philoxeroides - Dan Li; Xiao-Gai Wang; Jia-Xin Yang; Yu-Fei Hu; Wen-Yue Lyu; Jun-Cai Xin; Rui Zhang; Zhi-Huan Chen; Chao Si (Aquatic Ecology, 2024)

Enhancing the effluent prediction accuracy with insufficient data based on transfer learning and LSTM algorithm in WWTPs - Yadan Yu; Yangwu Chen; Shunbo Huang; Rui Wang; Yadong Wu; Houzhen Zhou; Xin Li; Zhouliang Tan (Journal of Water Process Engineering, 2024)

High-efficiency preparation of starch nanocrystals with small size and high crystallinity by ethanol-acid penetration and dry-heating pretreatment - Wen-Xuan Hu; Xin-Rui Hu; Fan Jiang; Yulian Zhu; Min Yang; Qin Dan; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Microplastics affect mosquito from aquatic to terrestrial lifestyles and are transferred to mammals through mosquito bites - Jian-hang Li; Xiao-hui Liu; Guo-rui Liang; He-ting Gao; Si-han Guo; Xin-yu Zhou; Dan Xing; Teng Zhao; Chun-xiao Li (Science of The Total Environment, 2024)

Modulator of TMB-associated immune infiltration (MOTIF) predicts immunotherapy response and guides combination therapy - Zheng-Yu Qian; Yi-Qian Pan; Xue-Xin Li; Yan-Xing Chen; Hao-Xiang Wu; Ze-Xian Liu; Martin Kosar; Jiri Bartek; Zi-Xian Wang; Rui-Hua Xu (Science Bulletin, 2024)

Energy-efficient trehalose-based polyester nanofiltration membranes for zero-discharge textile wastewater treatment - Xiongwei Luo; Lei Jiang; Rui Zhao; Yue Wang; Xin Xiao; Sabrine Ghazouani; Lihua Yu; Zhaohuan Mai; Hideto Matsuyama; Pengrui Jin (Journal of Hazardous Materials, 2024)

Leaching and evolution of anthocyanins and aroma compounds during Cabernet Sauvignon wine fermentation with whole-process skin-seed contact - Xue-Chen Yao; Hua-Lin Zhang; Xin-Rui Ma; Nong-Yu Xia; Chang-Qing Duan; Wei-Ming Yang; Qiu-Hong Pan (Food Chemistry, 2024)

Oxidative stress-activated Nrf2 remitted polystyrene nanoplastic-induced mitochondrial damage and inflammatory response in HepG2 cells - Menghao Guo; Yunjing Li; Shuyan Niu; Rui Zhang; Xin Shen; Yu Ma; Liqing Wu; Tianshu Wu; Ting Zhang; Meng Tang; Yuying Xue (Environmental Toxicology and Pharmacology, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Polysulfide regulation by defect-modulated Ta3N5− electrocatalyst toward superior room-temperature sodium-sulfur batteries - Zhen Zhang; Dan Luo; Jun Chen; Chuyin Ma; Matthew Li; Haoze Zhang; Renfei Feng; Rui Gao; Haozhen Dou; Aiping Yu; Xin Wang; Zhongwei Chen (Science Bulletin, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

An electrochemical sensor derived from Cu-BTB MOF for the efficient detection of diflubenzuron in food and environmental samples - Xian-Xian Ji; Yu-Long Liu; Xin-Yue Chang; Rui-Long Li; Fei Ye; Liu Yang; Ying Fu (Food Chemistry, 2023)

Molecular and functional characterization of golden pompano (Trachinotus blochii) TBK1 on IFN regulation - Jin-Feng Tong; Rui-Hai Gan; Lang Yu; Shao-Yang Bu; Jun-Long Sun; Xin Wen; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Nano-composite system of traditional Chinese medicine for ocular applications: molecular docking and three-dimensional modeling insight for intelligent drug evaluation - Xinyi Jiao; Xingru Peng; Xin Jin; Ning Liu; Yang Yu; Rui Liu; Zheng Li (Drug Delivery and Translational Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Phosphoproteomic Analysis Reveals the Predominating Cellular Processes and the Involved Key Phosphoproteins Essential for the Proliferation of Toxoplasma gondii - Xin-zhu Chen; Rui-xue Bai; Fei-yu Qin; Hong-juan Peng; Jin-feng Ren; Lang Hu; Yu-di Li; Cheng He (Acta Parasitologica, 2023)

Evaluating soil water movement and soil water content uniformity under sprinkler irrigation with different soil texture and irrigation uniformity using numerical simulation - Rui Chen; Hong Li; Jian Wang; Xin Guo; Yu Xiang (Journal of Hydrology, 2023)

Whole-genome analysis of the benzoic acid-degrading bacterium Bacillus halotolerans B28 to reveal its phytoprobiotic effects - Dandan Wang; Li Sun; Hong Yu; Chengkai Zhang; Xin Guan; Mengliang Wang; Rui Cheng; Chao Wang; Zhihong Xie (International Biodeterioration & Biodegradation, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

The evolution of insecticide resistance in the white backed planthopper Sogatella furcifera (Horvath) of China in the period 2014–2022 - Ya-Ting Liu; Xin-Yu Song; Bin Zeng; Wen-Jing Zhang; Xing-Yu Chen; Ze-Rui Feng; Hua-Yang Yu; Cong-Fen Gao; Shun-Fan Wu (Crop Protection, 2023)

Dietary acetate promotes growth and nutrients deposition in Nile tilapia (Oreochromis niloticus) through increasing acetyl-CoA-triggered energy production - Wen-Hao Zhou; Samwel M. Limbu; Yuan Luo; Rui-Xin Li; Jiong Ren; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Aquaculture, 2023)

Rapid determination of the relative configuration of diverse 8,4′-oxyneolignans by NMR analysis: Retrospective studies, improvement and structural revision - Peng Zhao; Li-Li Lou; Ben-Song Xin; Zhi-Yuan Li; Rui Guo; Wei-Yu Zhou; Tian-Ming Lv; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Astragaloside IV-mediated inhibition of oxidative stress by upregulation of ghrelin in type 2 diabetes–induced cognitive impairment - Rui-hua Zhang; Shan-shan Cao; Yong Shi; Xin Wang; Lei-lei Shi; Yu-han Zhang; Chao-jun Han; Bin Wang; Liang Feng; Ji-ping Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effects of hypoxia on the gill morphological structure, apoptosis and hypoxia-related gene expression in blunt snout bream (Megalobrama amblycephala) - Xin-xin Yu; Yan-rui Zhang; Shan-shan Li; Guo-dong Zheng; Shu-ming Zou (Fish Physiology and Biochemistry, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

Trehalose metabolism targeting as a novel strategy to modulate acid tolerance of yeasts and its application in food industry - Zhongpeng Guo; Moying Li; Zitao Guo; Rui Zhu; Yu Xin; Zhenghua Gu; Liang Zhang (Food Microbiology, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

The extraordinarily large vortex structure of Typhoon In-fa (2021), observed by spaceborne microwave radiometer and synthetic aperture radar - Ziyao Sun; Lina Bai; Xuesong Zhu; Xin Huang; Rui Jin; Hui Yu; Jie Tang (Atmospheric Research, 2023)

Transcriptome Analysis of the Mouse Medial Prefrontal Cortex in a Chronic Constriction Injury Model - Qi-Min Zheng; Zi-Rui Zhou; Xin-Yu Hou; Ning Lv; Yu-Qiu Zhang; Hong Cao (NeuroMolecular Medicine, 2023)

Transient analyses for China initiative Accelerator Driven System using the extended BELLA code - Guan Wang; Janne Wallenius; Rui Yu; Wei Jiang; Lu Zhang; Xin Sheng; Di Yun; Long Gu (Annals of Nuclear Energy, 2023)

Refined feature fusion for in-field high-density and multi-scale rice panicle counting in UAV images - Yao Chen; Rui Xin; Haiyan Jiang; Yonghuai Liu; Xiaoqi Zhang; Jialin Yu (Computers and Electronics in Agriculture, 2023)

Fluorescence enhancement of surface plasmon coupled emission by Au nanobipyramids and its modulation effect on multi-wavelength radiation - Kai-Xin Xie; Rui-Ping Huo; Xiu-Li Song; Qiao-Ling Liu; Yue Jiang; Yu-Han Li; Lu-Lu Dong; Jia-Xin Cheng (Analytica Chimica Acta, 2023)

In situ polymerization of polypyrrole in oil body for efficient solar-driven freshwater collection - Hongxiang Liu; Tianshu Zou; Xingyu Cui; Miao Ding; Biao Zhang; Xiaodong Yang; Yu Han; Shuwei Nie; Yuan Zhang; Enze Wang; Lili Wang; Yan Cheng; et al. (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Effects of polystyrene nanoplastic gestational exposure on mice - Xiaoke Wang; Zixuan Zhao; Xin Wang; Wenxuan Hu; Chao luo; Xiuyu Chu; Muzhou Qian; Rui Wang; Shali Yu; Qiyun Wu; Juan Tang; Xinyuan Zhao (Chemosphere, 2023)

Driving forces and variation in water footprint before and after the COVID-19 lockdown in Fujian Province of China - Fan Yu; Yuan Wang; Xin Liu; Jinru Yu; Dandan Zhao; Haijun Deng; Bin Guo; Rui Shi; Bowei Wu; Huayang Chen (Journal of Cleaner Production, 2023)

Wide-Scope Multi-residue analysis of pesticides in beef by gas chromatography coupled with quadrupole Orbitrap mass spectrometry - Xu Pang; Jing Qiu; Zhaoyang Zhang; Pi Li; Jiangtao Xing; Xin Su; Guiqiao Liu; Changyuan Yu; Rui Weng (Food Chemistry, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A20 ameliorates disc degeneration by suppressing mTOR/BNIP3 axis-mediated mitophagy - Xin Peng; Cong Zhang; Jia-Wei Gao; Feng Wang; Jun-Ping Bao; Zhi-Min Zhou; Rui Sun; Hang-Yu Ji; Cabral VLF; Xiao-Tao Wu (Genes & Genomics, 2023)

Canopy height, rather than neighborhood effects, shapes leaf herbivory in a tropical rainforest - Shuang Zhang; Guo‐Rui Xu; Yu‐Xin Zhang; Wen‐Fu Zhang; Min Cao (Ecology, 2023)
Factors shaping the interspecific variations in herbivory have puzzled ecologists for decades and several hypotheses have been proposed to explain interspecific variation in leaf herbivory. In a tropical rainforest in Yunnan Province, China, we collected 6732 leaves from 129 species with canopy heights ranging from 1.6 to 65.0 m above the ground. We tested the role of canopy height, the diversity, composition and structural heterogeneity of neighbors and leaf traits in shaping the interspecific variations in herbivory. Results show that leaf herbivory decreased with canopy height and specific leaf area (SLA) and increased with leaf size. However, neighboring species' diversity, composition, and structural heterogeneity showed no association with herbivory. Therefore, neither the visual apparency effect nor the associational resistance effect was detected in this hyperdiverse tropical rainforest. These findings highlight the importance of vertical structure in shaping herbivory patterns in natural communities.

Abundance and characteristics of microplastics in the Wanquan River estuary, Hainan Island - Tuan-Tuan Wang; Wang-Qing Tang; Dong-Hai Wu; Xin-Rui Yu; Guang-Yu Wang; Xing-Wei Cai; Shuai Shao; Sai Wang; Ling Mo; You-Sheng Liu; Guang-Guo Ying; Zhong-Bing Chen (Marine Pollution Bulletin, 2023)

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Immediate and long-term changes in the epidemiology, infection spectrum, and clinical characteristics of viral and bacterial respiratory infections in Western China after the COVID-19 outbreak: a modeling study - Tianshan Shi; Xin Zhao; Xiaoshu Zhang; Lei Meng; Donghua Li; Xinfeng Liu; Hongmiao Zheng; Deshan Yu; Tingrong Wang; Rui Li; Juansheng Li; Xiping Shen; et al. (Archives of Virology, 2023)

High density mapping of wheat stripe rust resistance gene QYrXN3517-1BL using QTL mapping, BSE-Seq and candidate gene analysis - Shuo Huang; Yibo Zhang; Hui Ren; Xin Zhang; Rui Yu; Shengjie Liu; Qingdong Zeng; Qilin Wang; Fengping Yuan; Ravi P. Singh; Sridhar Bhavani; Jianhui Wu; et al. (Theoretical and Applied Genetics, 2023)

The circadian regulation of extracellular ATP - Xin Wang; Yu-Ting Dong; Xiu-Ming Hu; Ji-Zhou Zhang; Nan-Rui Shi; Yan-Qin Zuo; Xu Wang (Purinergic Signalling, 2023)
Extracellular ATP is a potent signaling molecule released from various cells throughout the body and is intimately involved in the pathophysiological functions of the nervous system and immune system by activating P2 purinergic receptors. Recent increasingly studies showed that extracellular ATP exhibits circadian oscillation with an approximately 24-h periodicity, which participates in regulatory pathways of central oscillator suprachiasmatic nucleus and peripheral oscillator bladder, respectively. Oscillators modulate the protein expression of ATP release channels and ectonucleotidase activity through clock genes; indeed, real-time alterations of ATP release and degradation determine outcomes of temporal character on extracellular ATP rhythm. The regulatory pathways on extracellular ATP rhythm are different in central and peripheral systems. In this review, we summarize the circadian rhythm of extracellular ATP and discuss several circadian regulatory pathways in different organs via ATP release and degradation, to provide a new understanding for purinergic signaling in the regulatory mechanism of circadian rhythm and a potential target to research the circadian regulation of extracellular ATP in other circadian oscillators.

3D gravity anomaly inversion based on LinkNet - Hou-Pu Li; Rui Qi; Jia-Xin Hu; Yu-Xin Sun (Applied Geophysics, 2023)

High cholesterol intake remodels cholesterol turnover and energy homeostasis in Nile tilapia (Oreochromis niloticus) - Rui-Xin Li; Ling-Yun Chen; Samwel M. Limbu; Yu-Cheng Qian; Wen-Hao Zhou; Li-Qiao Chen; Yuan Luo; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Marine Life Science & Technology, 2023)
The roles of dietary cholesterol in fish physiology are currently contradictory. The issue reflects the limited studies on the metabolic consequences of cholesterol intake in fish. The present study investigated the metabolic responses to high cholesterol intake in Nile tilapia ( Oreochromis niloticus ), which were fed with four cholesterol-contained diets (0.8, 1.6, 2.4 and 3.2%) and a control diet for eight weeks. All fish-fed cholesterol diets showed increased body weight, but accumulated cholesterol (the peak level was in the 1.6% cholesterol group). Then, we selected 1.6% cholesterol and control diets for further analysis. The high cholesterol diet impaired liver function and reduced mitochondria number in fish. Furthermore, high cholesterol intake triggered protective adaptation via (1) inhibiting endogenous cholesterol synthesis, (2) elevating the expression of genes related to cholesterol esterification and efflux, and (3) promoting chenodeoxycholic acid synthesis and efflux. Accordingly, high cholesterol intake reshaped the fish gut microbiome by increasing the abundance of Lactobacillus spp. and Mycobacterium spp., both of which are involved in cholesterol and/or bile acids catabolism. Moreover, high cholesterol intake inhibited lipid catabolic activities through mitochondrial β-oxidation, and lysosome-mediated lipophagy, and depressed insulin signaling sensitivity. Protein catabolism was elevated as a compulsory response to maintain energy homeostasis. Therefore, although high cholesterol intake promoted growth, it led to metabolic disorders in fish. For the first time, this study provides evidence for the systemic metabolic response to high cholesterol intake in fish. This knowledge contributes to an understanding of the metabolic syndromes caused by high cholesterol intake or deposition in fish.

Dietary sodium acetate improves high-fat diet utilization through promoting differential nutrients metabolism between liver and muscle in Nile tilapia (Oreochromis niloticus) - Wen-Hao Zhou; Samwel M. Limbu; Rui-Xin Li; Yuan Luo; Jiong Ren; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Aquaculture, 2023)

Manganese-induced α-synuclein overexpression promotes the accumulation of dysfunctional synaptic vesicles and hippocampal synaptotoxicity by suppressing Rab26-dependent autophagy in presynaptic neurons - Zhuo Ma; Kuan Liu; Rui-feng Zhang; Zi-xin Xie; Wei Liu; Yu Deng; Xin Li; Bin Xu (Science of The Total Environment, 2023)

Evaluations of policy contagion for new energy vehicle industry in China - Cody Yu-Ling Hsiao; Rui Yang; Xin Zheng; Yi-Bin Chiu (Energy Policy, 2023)

Friction induced mechanochemistry: self-adaptive lubrication through in-situ tribo-click system - Rui Dong; Yunlei Zhang; Hao-Zhe Xu; Luyao Bao; Shuanhong Ma; Xin-Gang Wang; Qiangliang Yu; Meirong Cai; Feng Zhou; Weimin Liu (Chemical Engineering Journal, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

TREM2 and Microglia Contribute to the Synaptic Plasticity: from Physiology to Pathology - Chao-Ji Yu; Meng Wang; Rui-Yang Li; Tao Wei; Han-Chen Yang; Yun-Si Yin; Ying-Xin Mi; Qi Qin; Yi Tang (Molecular Neurobiology, 2023)

Effects of bepridil on early cardiac development of zebrafish - Ya-Lan Wei; Yu-Qing Lei; Zhou-Jie Ye; Xu-Dong Zhuang; Li-Ping Zhu; Xin-Rui Wang; Hua Cao (Cell and Tissue Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Habitat quality dynamics in China's first group of national parks in recent four decades: Evidence from land use and land cover changes - Xin Chen; Le Yu; Yue Cao; Yidi Xu; Zhicong Zhao; Youbo Zhuang; Xuehua Liu; Zhenrong Du; Tao Liu; Bo Yang; Lu He; Hui Wu; et al. (Journal of Environmental Management, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Clinical Decision on Disorders of Consciousness After Acquired Brain Injury: Stepping Forward - Rui-Zhe Zheng; Zeng-Xin Qi; Zhe Wang; Ze-Yu Xu; Xue-Hai Wu; Ying Mao (Neuroscience Bulletin, 2023)

Environmental and economic benefits of substituting chemical potassium fertilizer with crop straw residues in China - Junhui Yin; Dongjia Li; Jingyao Yu; Xin Bai; Wenjing Cui; Rui Liu; Minghao Zhuang (Environmental Science and Pollution Research, 2022)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

Compounding soils to improve cropland quality: A study based on field experiments and model simulations in the loess hilly-gully region, China - Yun-xin Huang; Zheng-jia Liu; Yan-sui Liu; Yu-rui Li; Xue-qi Liu (Journal of Mountain Science, 2022)

Identification of Ferroptotic Genes in Spinal Cord Injury at Different Time Points: Bioinformatics and Experimental Validation - Yu Kang; Qiangwei Li; Rui Zhu; Shuang Li; Xin Xu; Xuanming Shi; Zongsheng Yin (Molecular Neurobiology, 2022)

Long non-coding RNA RPL34-AS1 ameliorates oxygen–glucose deprivation-induced neuronal injury via modulating miR-223–3p/IGF1R axis - Xin-ya Wei; Tian-qi Zhang; Rui Suo; You-yang Qu; Yan Chen; Yu-lan Zhu (Human Cell, 2022)

Homocysteine-Induced Disturbances in DNA Methylation Contribute to Development of Stress-Associated Cognitive Decline in Rats - Shi-Da Wang; Xue Wang; Yun Zhao; Bing-Hua Xue; Xiao-Tian Wang; Yu-Xin Chen; Zi-Qian Zhang; Ying-Rui Tian; Fang Xie; Ling-Jia Qian (Neuroscience Bulletin, 2022)

Pelagic cyanobacterial nitrogen fixation in lakes and ponds of different latitudinal zones - Yan Li; Ye-Xin Yu; Shuo-Nan Ma; Rui-Ting Qiao; Yong-De Cui; Hai-Jun Wang; Hong-Zhu Wang (Aquatic Sciences, 2022)

Aberrant Gene Expression of Selenoproteins in Chicken Spleen Lymphocytes Induced by Mercuric Chloride - Jia-Hong Chu; Yu-Xue Yan; Xue-Wei Chen; Pei-Chao Gao; Lan-Xin Li; Rui-Feng Fan (Biological Trace Element Research, 2022)

Identification and Expression Analysis of the SBP-box Gene Family Related to Abiotic Stress in Tea Plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Hao Liu; Yu Wang; Jing Zhuang (Plant Molecular Biology Reporter, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Serine protease HtrA2/Omi regulates adaptive mitochondrial reprogramming in the brain cortex after ischemia/reperfusion injury via UCP2-SIRT3-PGC1 axis - Hao Meng; Lian-Kun Sun; Jing Su; Wan-Yu Yan; Yao Jin; Xin Luo; Xian-Rui Jiang; Hong-Lei Wang (Human Cell, 2022)

Numerical simulation study on the seepage characteristics of coal seam infusion effected by mining-induced stress - Yanbin Yu; Qilin Xin; Weimin Cheng; Jun Rui; Xin Zhang (Bulletin of Engineering Geology and the Environment, 2021)

Effects of organic acids on the chemotaxis profiles and biocontrol traits of antagonistic bacterial endophytes against root-rot disease in Panax notoginseng - Li Ma; Wu-Qin Wang; Rui Shi; Xue-Mei Zhang; Xin Li; Yu-Sen Yang; Ming He Mo (Antonie van Leeuwenhoek, 2021)

The mTOR/NF-κB Pathway Mediates Neuroinflammation and Synaptic Plasticity in Diabetic Encephalopathy - Ting Xu; Jiao Liu; Xin-rui Li; Yinghua Yu; Xuan Luo; Xian Zheng; Yuan Cheng; Pei-quan Yu; Yi Liu (Molecular Neurobiology, 2021)

Overexpression of T-type calcium channel Cav3.1 in oral squamous cell carcinoma: association with proliferation and anti-apoptotic activity - Rui-Fang Li; Qi-Wen Man; Jin-Yuan Liu; Yue-Yu Zheng; Xin Gao; Hai-Ming Liu (Journal of Molecular Histology, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Two new dihydroisocoumarins with antimicrobial activities from the fungus Penicillium sp. XR046 collected from Xinren coal area - Guo-Bo Xu; Fei-Yu Yang; Xin-Yu Wu; Rui Li; Meng Zhou; Bing Wang; Xiao-Sheng Yang; Ting-Ting Zhang; Shang-Gao Liao (Natural Product Research, 2021)

Antifungal Effect of Long Noncoding RNA 9708-1 in the Vulvovaginal Candidiasis Murine Model - Ying Wu; Lisha Jiang; Lingling Zhang; Xia Liu; Lina Yan; Ting Luan; Can Rui; Zhiyuan Mao; Chong Fan; Yu Liu; Ping Li; Xin Zeng (Mycopathologia, 2021)
Vulvovaginal candidiasis (VVC) caused by Candida spp. affects 70–75% of women at least once during their lives. We aim to elucidate the potential mechanism of VVC and investigate the therapeutic effects of long noncoding RNA 9708-1. Female BALB/c mice were randomized to four treatment groups, including the blank control group, VVC control group, vehicle control group and lncRNA 9708-1-overexpressed group. Mice were euthanized on Day 4, Day 7 and Day 14 after treatment. Colony-forming unit (CFU) was measured, and the inflammation was detected by hematoxylin and eosin (H&E). Gene and protein expression levels of lncRNA 9708-1 and FAK were determined by real-time PCR, Western blot and immunohistochemistry. The overexpression of lncRNA 9708-1 significantly decreased the fungal load from Day 4 to 7. H&E staining indicated that the impaired histological profiles were improved in lncRNA 9708-1-overexpressed group. LncRNA 9708-1 led to a significant increase in FAK level of vagina tissue which is expressed mainly in epithelial basal layer. This study suggests that lncRNA 9708-1 played a protective role on murine experimental VVC by upregulating the expression levels of FAK.

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Rescue effects of Se-enriched rice on physiological and biochemical characteristics in cadmium poisoning mice - Yang Su; Ling Li; Muhammad Umer Farooq; Xin Huang; Tengda Zheng; Yu Jie Zhang; Hla Hla Ei; Faiz Hussain Panhwar; Zhichen Tang; Rui Zeng; Yuanke Liang; Xiaoying Ye; et al. (Environmental Science and Pollution Research, 2021)

Development of global soil erosion research at the watershed scale: a bibliometric analysis of the past decade - Xuan Huang; Kai-Rui Wang; Yu-wen Zou; Xin-Chun Cao (Environmental Science and Pollution Research, 2021)

Microbial community changes in the digestive tract of the clam Meretrix petechialis in response to Vibrio parahaemolyticus challenge - Hongxia Wang; Xin Yue; Jiajia Yu; Rui Wang; Shuangshuang Teng; Jun Fang; Baozhong Liu (Journal of Oceanology and Limnology, 2021)

Constructed wetlands integrated with microbial fuel cells for COD and nitrogen removal affected by plant and circuit operation mode - Huiyang Wen; Hui Zhu; Baixing Yan; Brian Shutes; Xiangfei Yu; Rui Cheng; Xin Chen; Xinyi Wang (Environmental Science and Pollution Research, 2021)

Energy conservation and carbon reduction potential for solid waste in China - Minxi Wang; Zhi Li; Lu Chen; Ping Liu; Rui Zhang; Wei Liu; Yu Ma; Yajie Wang; Xin Li (Environmental Science and Pollution Research, 2020)

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Heritability of resistance-related gene expression traits and their correlation with body size of clam Meretrix petechialis - Fengjuan Jiang; Xin Yue; Shujing Zhang; Jiajia Yu; Rui Wang; Baozhong Liu; Hongxia Wang (Journal of Oceanology and Limnology, 2020)

Correction to: Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Evaluation on activation energy of deposited clay based on thermo-gravimetric analysis (TGA) and four kinetics models - Rui-xin Yan; Jian-bing Peng; Yan-jun Shen; Yu-liang Zhang; Lin-jun Gu; Shao-kai Wang (Bulletin of Engineering Geology and the Environment, 2020)

Structural characterization and immunosuppressive activity of a new pregnane glycoside from Epigynum cochinchinensis - Yu-Ting Shao; Yan Zhao; Hong Zhang; Meng-Jun Jiang; Afsar Khan; Sheng-Bao Cai; Tian-Rui Zhao; Gui-Guang Cheng; Jian-Xin Cao (Natural Product Research, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

ANKRD49 inhibits etoposide-induced intrinsic apoptosis of GC-1 cells by modulating NF-κB signaling - Xia Zhou; Wen-tao Wang; Jia Sun; Hong-yan Liu; Xin-yan Bai; Juan-juan Liu; Bao-feng Yu; Rui Guo; Hai-long Wang (Molecular and Cellular Biochemistry, 2019)

Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2019)

Analysis of the Effects of a Rotating Rock on Rockfall Protection Barriers - Xin Qi; Xiangjun Pei; Rui Han; Yafeng Yang; Qingcheng Meng; Zhixiang Yu (Geotechnical and Geological Engineering, 2018)

A new cinnamic acid glycoside from roots of Heracleum dissectum - Zhi-Gang Wang; Jie Mi; Xin-Rui Wang; Ya-Yu Huo; Ya-Jie Peng; Hai-Min Zhang; Yang Gao; Hai-Long Zhang (Natural Product Research, 2018)

Structural Transformation Detection Contributes to Screening of Behaviorally Active Compounds: Dynamic Binding Process Analysis of DhelOBP21 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Guangqiang Yu; Shan-Cheng Yi; Yinan Zhang; De-Xin Kong; Man-Qun Wang (Journal of Chemical Ecology, 2017)

A simple method for removing low-density granulocytes to purify T lymphocytes from peripheral blood mononuclear cells - Si-gong Zhang; Yu-xin Song; Xiao-ming Shu; Hai-li Shen; Han-bo Yang; Rui-xue Duo; Guo-chun Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Folate-Functionalized Lipid Nanoemulsion to Deliver Chemo-Radiotherapeutics Together for the Effective Treatment of Nasopharyngeal Carcinoma - Ying Liu; Xue-Min Yu; Rui-Jie Sun; Xin-Liang Pan (AAPS PharmSciTech, 2017)

Demethyleneberberine alleviates inflammatory bowel disease in mice through regulating NF-κB signaling and T-helper cell homeostasis - Ying-Ying Chen; Rui-Yan Li; Mei-Jing Shi; Ya-Xing Zhao; Yan Yan; Xin-Xin Xu; Miao Zhang; Xiao-Tong Zhao; Yu-Bin Zhang (Inflammation Research, 2017)

Molecular cloning and characterization of α-amylase/subtilisin inhibitor from rhizome of Ligusticum chuanxiong - Ji-hua Yu; Yang-yang Li; Mian Xiang; Jian-quan Zhu; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2017)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Effects of short-term inflammatory and/or hypoxic pretreatments on periodontal ligament stem cells: in vitro and in vivo studies - Yang Yu; Chun-Sheng Bi; Rui-Xin Wu; Yuan Yin; Xi-Yu Zhang; Ping-Heng Lan; Fa-Ming Chen (Cell and Tissue Research, 2016)

High-level expression of a novel recombinant human plasminogen activator (rhPA) in the milk of transgenic rabbits and its thrombolytic bioactivity in vitro - Shaozheng Song; Xin Ge; Yaobin Cheng; Rui Lu; Ting Zhang; Baoli Yu; Xueqiao Ji; Zhengqiang Qi; Yao Rong; Yuguo Yuan; Yong Cheng (Molecular Biology Reports, 2016)

Simulating land use change by integrating landscape metrics into ANN-CA in a new way - Xin Yang; Yu Zhao; Rui Chen; Xinqi Zheng (Frontiers of Earth Science, 2016)

Optimization of operation conditions for the mitigation of nitrous oxide (N2O) emissions from aerobic nitrifying granular sludge system - Rui-Ting Liu; Xin-Hua Wang; Yan Zhang; Ming-Yu Wang; Ming-Ming Gao; Shu-Guang Wang (Environmental Science and Pollution Research, 2016)

Molecular cloning and characterization of caffeic acid 3-O-methyltransferase from the rhizome of Ligusticum chuanxiong - Juan-Juan Li; Gan Zhang; Ji-hua Yu; Yang-yang Li; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2015)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Gabapentin Enhances the Morphine Anti-Nociceptive Effect in Neuropathic Pain via the Interleukin-10-Heme Oxygenase-1 Signalling Pathway in Rats - Yu-Hua Bao; Quan-Hong Zhou; Rui Chen; Hao Xu; Lu-Lu Zeng; Xin Zhang; Wei Jiang; Dong-Ping Du (Journal of Molecular Neuroscience, 2014)

Overexpression of PeHSF mediates leaf ROS homeostasis in transgenic tobacco lines grown under salt stress conditions - Zedan Shen; Mingquan Ding; Jian Sun; Shurong Deng; Rui Zhao; Meijuan Wang; Xujun Ma; Feifei Wang; Huilong Zhang; Zeyong Qian; Yue Hu; Rui Yu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Photodegradation of Tri (2-chloroethyl) Phosphate in Aqueous Solution by UV/H2O2 - Xin-Chao Ruan; Rui Ai; Xiao Jin; Qing-Fu Zeng; Ze-Yu Yang (Water, Air, & Soil Pollution, 2013)

CSMD1 exhibits antitumor activity in A375 melanoma cells through activation of the Smad pathway - Ming-Rui Tang; Yu-Xin Wang; Shu Guo; Si-Yuan Han; Di Wang (Apoptosis, 2012)

Involvement of p38MAPK/NF-κB Signaling Pathways in Osteoblasts Differentiation in Response to Mechanical Stretch - Liang Wang; Jian-yu Li; Xi-zheng Zhang; Lu Liu; Zong-ming Wan; Rui-xin Li; Yong Guo (Annals of Biomedical Engineering, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Evaluation of the Use of SCAR Markers for Screening Genetic Diversity of Lentinula edodes Strains - Jing-Yu Liu; Zheng-He Ying; Fang Liu; Xin-Rui Liu; Bao-Gui Xie (Current Microbiology, 2012)

Effects of ginkgolide B on neuronal discharges in paraventricular nucleus of rat hypothalamic slices - Yue Lin; Ru Wang; Xin Wang; Rui-Rong He; Yu-Ming Wu (Neuroscience Bulletin, 2008)

The glycosides from Lomatogonium rotatum - Yu-Lin Li; You-Rui Suo; Zhi-Xin Liao; Li-Sheng Ding (Natural Product Research, 2008)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)